2022
DOI: 10.3389/fphar.2022.948600
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory mechanisms of tetramethylpyrazine on central nervous system diseases: A review

Abstract: Central nervous system (CNS) diseases can lead to motor, sensory, speech, cognitive dysfunction, and sometimes even death. These diseases are recognized to cause a substantial socio-economic impact on a global scale. Tetramethylpyrazine (TMP) is one of the main active ingredients extracted from the Chinese herbal medicine Ligusticum striatum DC. (Chuan Xiong). Many in vivo and in vitro studies have demonstrated that TMP has a certain role in the treatment of CNS diseases through inhibiting calcium ion overload… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 205 publications
0
6
0
Order By: Relevance
“…Secondary injury of SCI is often a more important cause of neuron loss. Glutamate excitatory toxicity is a common mechanism of neuronal tissue death at this stage [ 50 ]. Reduced extracellular Zn 2+ concentration induced by trauma can lead to dysregulation of the NF-κB signaling pathway, which leads to glutamate excitotoxicity of astrocytes and promotes apoptosis of oligodendrocytes[ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Secondary injury of SCI is often a more important cause of neuron loss. Glutamate excitatory toxicity is a common mechanism of neuronal tissue death at this stage [ 50 ]. Reduced extracellular Zn 2+ concentration induced by trauma can lead to dysregulation of the NF-κB signaling pathway, which leads to glutamate excitotoxicity of astrocytes and promotes apoptosis of oligodendrocytes[ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, no rescue experiments were conducted in this study. Thus, drawing upon the extant literature, 12,50 we postulated that the GMPT hydrogel may modulate endothelial cell apoptosis by regulating the PI3K/AKT axis, thereby preserving the integrity of the barrier. In addition, the destruction of the BSCB is not solely attributable to apoptosis in endothelial cells, but also to the loss of tight junction proteins, which are present between endothelial cells to maintain intercellular spaces and regulate cellular polarity.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, TMP has significant vascular protective effects. 12 The latest meta-analysis indicated that injecting TMP as an adjunctive treatment seemed effective in enhancing the efficacy of acute cerebral infarction and improvement in neurological deficit scores of patients. 13 Meanwhile, diverse pharmacological activities of TMP in protecting barrier integrity have also been validated.…”
Section: Introductionmentioning
confidence: 99%
“…Ligustrazine also reduces the concentration of ROS and malondialdehyde (MDA) while upregulating the activity of superoxide to relieve oxidative stress. Furthermore, it intervenes in the course of ischemia-reperfusion by reducing Ca2 + overload and trough amino acid excitotoxicity, as well as improving synaptic ultrastructure to enhance synaptic plasticity ( Liu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%